Overexpression of Water-Responsive Genes Promoted by Elevated CO2 Reduces ROS and Enhances Drought Tolerance in Coffea Species - Marques, Isabel (2023)
Project UID/AGR/04129/2020 (LEAF). Fellowships from the Conselho Nacional de Desenvolvimento Cientifico e Tecnologico, Brazil (CNPq) for F.L.P. and F.M.D. and the Fundação de Amparo á Pesquisa do Estado de Minas Gerais, Brazil (FAPEMIG, project CRA-RED-00053-16; APQ01512-18, to F.M.D.) are also greatly acknowledged. Publisher Copyright: © 2023 by the authors.